2022
DOI: 10.1002/adhm.202201749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of a Biomimetic Mechanical Environment on Cancer Invasion and Matrix Remodeling

Abstract: The stiffness of tumors and their host tissues is much higher than most hydrogels, which are conventionally used to study in vitro cancer progression. The tumoroid assay is an engineered 3D in vitro tumor model that allows investigation of cancer cell invasion in an environment that is biomimetic in terms of extracellular matrix (ECM) composition and stiffness. Using this model, the change in matrix stiffness by epithelial colorectal cancer cells is systematically characterized by atomic force microscopy inden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 73 publications
2
18
0
Order By: Relevance
“…The model system used in this work is a PAA gel; therefore, its stiffness was not susceptible to MMP degradation and softening. It was recently shown that a compressed collagen gel (elastic modulus, 4 kPa) treated with recombinant MMP-1 (800 ng/ml) softened from 4 to 1 kPa over 5 hours ( 56 ). While this would suggest we could see substantial softening, we note that the highest concentration of MMP-1 observed in our cultures was on the order of 10 ng/ml (80-fold less), which suggests that this effect would be slower or lessened—particularly as the stiffness in metastatic HGSOC is an order of magnitude higher.…”
Section: Discussionmentioning
confidence: 99%
“…The model system used in this work is a PAA gel; therefore, its stiffness was not susceptible to MMP degradation and softening. It was recently shown that a compressed collagen gel (elastic modulus, 4 kPa) treated with recombinant MMP-1 (800 ng/ml) softened from 4 to 1 kPa over 5 hours ( 56 ). While this would suggest we could see substantial softening, we note that the highest concentration of MMP-1 observed in our cultures was on the order of 10 ng/ml (80-fold less), which suggests that this effect would be slower or lessened—particularly as the stiffness in metastatic HGSOC is an order of magnitude higher.…”
Section: Discussionmentioning
confidence: 99%
“…Having established the emergence of enhanced tissue stiffening, we investigated the possible cause of the stiffening. Specifically, we constructed a model to evaluate the contribution of active forces applied by cells and changes in ECM mechanics (41)(42)(43)(44). This highlighted that cell-generated forces could play a major role in the emergent stiffening of the vascular networks (fig.…”
Section: Active Cellular Force Generation Is the Major Contributor To...mentioning
confidence: 99%
“…Furthermore, ECM properties can be tuned to have stiffnesses similar to human tissues, such as breast, bone marrow, and brain, which are all common sites of breast cancer extravasation. [ 41 , 42 , 43 , 44 ]…”
Section: D Assay For Probing Extravasation Mechanicsmentioning
confidence: 99%